Financial well-being and physical health related quality of life among persons incarcerated in jail - Panisch, Lisa S. (Journal of crime and justice, 2019)
The current study aimed to describe financial well-being and physical health-related quality of life (HRQoL) in a convenience sample of incarcerated persons attenuated by gender and minority status. Financial well-being and physical HRQoL are inextricably linked to one another and to successful reentry among incarcerated persons. Survey respondents (n = 299) were incarcerated at a Southeastern county jail. Frequencies, descriptive statistics, and ANOVA and ANCOVA were used to meet the aforementioned aims. Incarcerated men reported higher levels of HRQoL, lower levels of financial anxiety, and higher levels of financial health than women. ANOVA results indicated statistically significant differences among groups regarding financial well-being and physical HRQoL. Subgroup differences in physical HRQoL were no longer statistically significant upon inclusion of financial well-being variables using ANCOVA. Future investigators are encouraged to capture time to release measures and recidivism data to examine the relationships among financial well-being and physical HRQoL and to explore predictive capabilities of financial self-efficacy, financial health, and financial anxiety on health and reentry outcomes among incarcerated persons.